Does the compositional effect explain the association between rates of in-migration and out-migration? - Hannu Tervo (European Regional Science Association (ERSA), 2001)
A common empirical observation obtained in many countries is that regions with a high gross out-migration per capita also tend to have a high gross in-migration per capita, and vice versa. Another common and curious observation is a positive correlation between out-migration rate and net-migration rate. This has been interpreted to mean that out-migration is independent of the economic characteristics of the region. A number of explanations has been suggested to explain the positive relationship between the rates of out-migration and in-migration. According to the compositional effect- explanation, a region that attracts migrants grow to have a population which is more migration prone, thus also increasing out-migration from the region. Another explanation is related to the idea of "vacancy chain": the departure of residents leaves vacated positions such as jobs and houses for new-comers, thus increasing in-migration. The economic activities that make an area attractive may also increase turnover and thus out-migration. If jobs are easily available, this attracts in-migrants, but may also make workers to leave the jobs easily, thus adding out-migration. This paper analyses the relationships between the components of migration in Finland in the 1990s, and their development since 1975. Inter-regional migration, and regional concentration with it, accelerated pronouncedly in Finland after the mid 1990s. Migration research, which also gained popularity, is dominated by the analysis of net-migration and analyses based on micro-data, but the analysis related to gross migration is few in number. Therefore, we have only limited understanding on the behaviour and relationships of the out-, in- and net-migration rates in Finland. The results show that the rate of out-migration is positively related to the rate of in- migration, but negatively related to the rate of net-migration. The first result is in accordance with the common result, but the second is not. Out-migration seems to be related with the economic characteristics of the region in Finland, and therefore the correlation between the rates of out- and net-migration is negative. The push factors work in Finland, which result has also been obtained from migration studies based on micro-data. In analysing the relationship between the out- and in-migration rates, this paper also analyses the significance of the compositional effect by utilizing micro-based data from the period of 1987-96. In this analysis, the population is divided into two parts, those who have moved before and those who have not, and the relationships between the components of migration are analysed separately in these two groups. Accordingly, we swift from the use of microdata to the use of macro (regional) data in this analysis.
Keywords: 330